The regional input-output model for East Malaysia region: construction and application - Hassan, Mohd Khairul Hisyam; Mohd Noor, Zaleha; Ismail, Normaz Wana; Radam, Alias; Abdul Rashid, Zakariah (Human Resource Management Academic Research Society, 2017)
This study examines the importance of regional development planning to economic growth through the construction of regional input-output table for East Malaysia. It is particularly important because only limited past studies have been conducted on the construction of regional input-output table at the regional or state level in Malaysia and also, the usage of input-output model has received much attention in many countries as a planning tool for economic development. In the case of East Malaysia, it was carried out through applying the non-survey based method, namely RAS technique. Through the backward and forward linkage and multipliers analysis, this study found that agriculture and livestock; mining and quarrying; food manufacturing; petroleum products; and electronics and non-electronics; sectors were among the sectors with the highest backward linkage and multiplier coefficients in the East Malaysia region. So, by putting additional investment into these sectors will generate more output to the overall economic performance of these regions because of the ability of these sectors to attract the other sectors in the economy.